COMPREHENDING THE TOPIC OF A PARAGRAPH: A FUNCTIONAL IMAGING STUDY OF A COMPLEX LANGUAGE PROCESS - Tomitch, Lêda Maria Braga; Newman, Sharlene D.; Carpenter, Patricia A.; Just, Marcel Adam (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2008)
This study uses fMRI (functional magnetic resonance imaging) to investigate the brain activity in a set of cortical areas in the task of main idea identification, when the topic sentence was presented in first versus in last position in a three-sentence paragraph. The participants were eight right-handed undergraduate students from Carnegie Mellon University, six male and 2 female, all native speakers of English. Each participant read twelve paragraphs, six in which the topic sentence was paragraph initial and six in which it was paragraph final, and each paragraph was presented word by word in the center of a screen, inside the scanner. The major finding of the current study is the differential response observed in the left and right hemispheres as to the location of the topic sentence within the paragraph. The left temporal region showed greater activation when the topic sentence was in final position than in initial position. The right temporal region, on the other hand, was affected only by sentence type, showing a greater response to topic sentences than support sentences, regardless of their location within the paragraph.